Worker’s Competency and Perception toward Safety and Health on Forest Harvesting Operation in Indonesian Long Rotation Plantation Forest - Efi Yuliati Yovi; Seca Gandaseca; I Nyoman Adiputra (Institut Pertanian Bogor (IPB University), 2012)
Despite of prevention measures such as government regulations and recommendations through technical and managerial researches, unsafe working practices are still a common practice in Indonesia's forestry work, especially in tree harvesting operation. In order to determine competency level of both field supervisor and workers as a baseline in developing participatory occupational safety and health (OSH) protection program, a previously developed competency assessing instrument has been modified. Further, the redesigned instrument was used to verify competency level of field supervisor and forestry workers (chainsawman, hauling workers, and truck drivers) from 6 different forest sites with similar working method. Results showed that both group of respondents had overestimated their competency level in practical aspect, indicated by the gap existence between OSH self-perception value and the standard-based assessment value. The gap significantly occurred in knowledge, skill, and attitude elements; however working attitudes rest in the worst level. This finding then indicated that improving working attitude should be taken as the goal priority in the OSH protection programs in Indonesia. In short, when the discussion is pointed to practical activities, OSH protection program should adapt such strategies which put serious consideration on control mechanism.